Pengaruh Brand Image, Price Dan Brand Ambassador Terhadap Keputusan Pembelian Sepatu Merk Vans (Studi Pada Konsumen Sepatu Vans Di Kota Malang) - Miftafarij, Ahmad; Basalamah, Muhammad Ridwan; Wahono, Budi (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract                                                                                                       The purpose of this research is to examine the influence of Brand Image, Price, and Brand Ambassador on Purchase Decision. This study employs a quantitative explanatory research design with purposive sampling as the sampling method. A total of 95 respondents, who are consumers of Vans shoes, participated in this study. The data were processed using IBM SPSS version 27. The findings indicate that the variables Brand Image (X1), Price (X2), and Brand Ambassador (X3) each have a significant partial effect on Purchase Decision (Y). Based on the F-test, the calculated F-value is 89.628, with a significance level of < 0.05 (0.01 < 0.05). The coefficient of determination shows that Brand Image (X1), Price (X2), and Brand Ambassador (X3) collectively influence Purchase Decision by 73.9%, while the remaining 26.1% is influenced by other variables not included in this study. Keywords: Brand Image, Price, Brand Ambassador, Purchase Decision